Pengaruh Literasi Keuangan Dan Lingkungan Sosial Terhadap Perilaku Keuangan Mahasiswa FEBI UIN STS Jambi - Fuji Agustina; Efni Anita; Muthmainnah Muthmainnah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to determine and analyze the effect of financial literacy and the social environment on the financial behavior of FEBI students at UIN STS Jambi. The method used in this study is a quantitative method, and the data analysis method used is the coefficient of determination test. The samples in this study were 96 samples of FEBI students at UIN STS Jambi class of 2019-2022. The results of the study show that partially, financial literacy has no effect on financial behavior and the social environment has a positive effect on financial behavior. Simultaneously, it shows that financial literacy and social environment variables have a significant effect on the financial behavior of FEBI students at UIN STS Jambi. The results of the calculation of the coefficient of determination show that financial literacy and social environment variables have an influence of 24.8% and the remaining 75.2% is influenced by other variables outside of this study.